4(2n+4)=6(9n+8)+6

Simple and best practice solution for 4(2n+4)=6(9n+8)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2n+4)=6(9n+8)+6 equation:



4(2n+4)=6(9n+8)+6
We move all terms to the left:
4(2n+4)-(6(9n+8)+6)=0
We multiply parentheses
8n-(6(9n+8)+6)+16=0
We calculate terms in parentheses: -(6(9n+8)+6), so:
6(9n+8)+6
We multiply parentheses
54n+48+6
We add all the numbers together, and all the variables
54n+54
Back to the equation:
-(54n+54)
We get rid of parentheses
8n-54n-54+16=0
We add all the numbers together, and all the variables
-46n-38=0
We move all terms containing n to the left, all other terms to the right
-46n=38
n=38/-46
n=-19/23

See similar equations:

| 6x+8/2=3x/2+18 | | 2x-3=1x+3 | | 1/2h(3+7)=20 | | 20=1/2h(3+7) | | r^2-10r-144=0 | | 2a2–46a+252=0 | | 6(x-1)/3=2(x+4)/6 | | 2x^2-24x-33=0 | | x/2x+3=11 | | 0.14(y-9)+0.18y=0.20y-0.3 | | 2x^2-19x+104=0 | | -2(x+2)-4=0 | | 20y2-31y+12=0 | | 36c-12=45c+45 | | W2+6w-11=0 | | (3x^2)-4x=0 | | -2(5t-5)+5t=6t-9 | | W3+6w-11=0 | | x=8-20-3 | | (4x-1)=x+36 | | x=8-20+3 | | 88x-11x^2=0 | | x²+16x+64=0 | | 3/5*x=40 | | 18-4x=7+7x | | 2*(x–3)–7=18–5*(x+4) | | 2x+3-7x=18-5x-20 | | 3g^2+32g-256=0 | | 7x−8=−71 | | 3(1x+1)=27 | | 5(2x+10=170 | | 5(3x+4)=170 |

Equations solver categories